2018
DOI: 10.3390/md16090298
|View full text |Cite
|
Sign up to set email alerts
|

Trichormus variabilis (Cyanobacteria) Biomass: From the Nutraceutical Products to Novel EPS-Cell/Protein Carrier Systems

Abstract: A native strain of the heterocytous cyanobacterium Trichormus variabilis VRUC 168 was mass cultivated in a low-cost photobioreactor for a combined production of Polyunsaturated Fatty Acids (PUFA) and Exopolymeric Substances (EPS) from the same cyanobacterial biomass. A sequential extraction protocol was optimized leading to high yields of Released EPS (REPS) and PUFA, useful for nutraceutical products and biomaterials. REPS were extracted and characterized by chemical staining, Reversed Phase-High-Performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 91 publications
(111 reference statements)
3
13
0
Order By: Relevance
“…The presence of non-carbohydrate substituents is proven to act as biological weapons, showing anti-viral, anti-microbial, anti-tumoral activity [14][15][16][17]. Their potential has been already explored as drug delivery technology [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of non-carbohydrate substituents is proven to act as biological weapons, showing anti-viral, anti-microbial, anti-tumoral activity [14][15][16][17]. Their potential has been already explored as drug delivery technology [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, TST, due to the capability of detoxifying cyanide, has been investigated for its use in many environmental and biomedical biotechnologies (see Table 1 ). Among the most important ones, in this review we emphasize the removal and biodegradation of cyanide from different environmental compartments [ 143 , 144 ], the production of carrier-based therapeutic catalytic bio-scavengers against cyanide [ 145 , 146 ], the reduction of toxic HCN concentration in ruminant animals’ diet [ 147 ] and the development of innovative biosensors for cyanide detection [ 148 ].…”
Section: Biotechnological Application Of Tstmentioning
confidence: 99%
“…They showed that DADS is not a more efficient sulfur donor than TS; however, the use of external TST significantly enhanced the in vivo efficacy of both sulfur donor-nitrite combinations, indicating the potential usefulness of enzyme nano-delivery systems in developing antidotal therapeutic agents [ 178 ]. Recently, an alternative approach was proposed by Bellini et al which produced a photo-polymerizable hybrid hydrogel using exopolymeric substances (REPS) extracted by the cyanobacterium Trichormus variabilis VRUC 168, with the addition of polyethylene glycol diacrylated (PEGDa) [ 146 ]. Bellini and colleagues used the recombinant TST from Azotobacter vinelandii [ 26 , 30 , 56 , 89 ] as an enzymatic model to assess the enzyme carrier ability of REPS-hydrogel.…”
Section: Biotechnological Application Of Tstmentioning
confidence: 99%
“…The RPS produced by the cyanobacterium Trichormus variabilis VRUC 168 were combined with diacrylated polyethylene glycol to produce photopolymerizable hybrid hydrogels [35]. These gels were stable over time and resistant to dehydration and spontaneous hydrolysis, being successfully used as matrices for the active form of the enzyme thiosulfate:cyanide sulfur transferase, as well as for 3D culture system of human mesenchymal stem cells (hMSCs).…”
Section: Development and Possible Applications Of Cyanobacterial Ementioning
confidence: 99%
“…In the last years, significant advances were made on the characterization of cyanobacterial EPS [13,14,15,16] and the validation of their biotechnological and biomedical potential as metal chelators [15,17,18,19,20,21], flocculating, emulsifying or rheology modifiers [22,23,24,25] and/or agents with valuable biological activities (e.g., antiviral, antimicrobial, anticoagulant, antitumor) [26,27,28,29,30,31,32,33,34]. However, the development of biomaterials based on these polymers has only recently started to be explored [35,36,37,38,39]. In this context, the repertoire of cyanobacterial EPS-based biomaterials can be significantly expanded through the development of strategies to obtain designer biopolymers with specialized features, by either metabolic engineering and/or chemical functionalization.…”
Section: Introductionmentioning
confidence: 99%